DIDACTIC MODEL OF DEVELOPMENT OF INCLUSIVE COMPETENCE OF FUTURE SPEECH THERAPISTS - Nilufar Abidova; Zukhra Akhmedova; Gulnoza Salikhova (The Bioscan, 2024)
In this article, the problem of the didactic model of developing the inclusive competence of future speech therapists is studied. Together with this, the components of readiness for inclusive education and inclusive competence are described, the ideas, essence, principles, opportunities and social importance of inclusive education are discussed. Based on the competence approach, the main content directions implemented by the didactic model of the inclusive competence development of future speech therapists are indicated.